Clinician-driven value scoring to prioritise quality actions: a study of general medicine hospital pharmacists. Issue 2 (17th March 2014) - Loewen, Peter; de Lemos, Jane; Woo, Stephanie
Abstract: Background: As with many clinical services, the number of patients requiring clinical pharmacist care exceeds the supply of those trained to provide it, so leaders and clinicians must make choices about which services to provide. A 'Quality Actions' (QA) framework has been proposed that provides for clinician-driven, systematic, transparent quantitative characterisation of individual QAs in terms of their value. This forms a basis for enhancement of quality of care. Objective: To evaluate whether the value score is a feasible means of characterising the relative value of QAs among inpatient general medical pharmacists in a large multi-center health region. Methods: Prospective study. In phase I, a set of six commonly performed QAs were identified by practitioners. In phase II, respondents scored all the QA elements across the six study QAs. Value scores were computed, the QAs ranked, and agreement among raters was assessed using intraclass correlation coefficients (ICCs). Sensitivity analyses were conducted to assess robustness of the rankings. Key findings: Six study QAs were identified in phase I, and 43 pharmacists (43%) participated in phase II. The value scores were generally distinguishable and robust to changes in weighting strategies. The ICC across all variables was 0.48 (95% CI 0.38–0.62), indicating good overall agreement. Vancomycin dosing showed excellent agreement, whereas streamlining of antimicrobial therapy and warfarin dosing in atrial fibrillation had the poorest agreement. Conclusions: It is feasible to develop a rank-ordered set of quality actions using a clinician-driven value score system. Good agreement between clinicians can be achieved using this system, and it is capable of identifying areas of disagreement, which may foster dialogue and focus educational efforts. Using this system may assist clinical service prioritisation and quality of care enhancement efforts.